2023
DOI: 10.1108/jabs-08-2022-0291
|View full text |Cite
|
Sign up to set email alerts
|

Intentional model of MSMEs growth: a tripod-based view and evidence from Indonesia

Abstract: Purpose The purpose of this study is to explore growth models based on “industry-based capabilities”, “resources-based capabilities” and “institution-based capabilities” in the context of the determinants of micro, small and medium enterprises’ (MSMEs) actors’ intention to grow. Design/methodology/approach This study involved 188 owners/managers of MSMEs. The analysis was conducted using partial least squares structural equation modelling. Moreover, the importance-performance map analysis package is used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 107 publications
(178 reference statements)
0
1
0
Order By: Relevance
“…This result is consistent with the research conducted by (Kurdi et al, 2023). Furthermore, the study conducted by (Utama et al, 2024) supports these findings, indicating that factors such as access to finance, technology, and infrastructure have a positive impact on the performance of MSMEs.…”
Section: Statistical Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…This result is consistent with the research conducted by (Kurdi et al, 2023). Furthermore, the study conducted by (Utama et al, 2024) supports these findings, indicating that factors such as access to finance, technology, and infrastructure have a positive impact on the performance of MSMEs.…”
Section: Statistical Resultssupporting
confidence: 90%
“…Therefore, MSMEs are crucial for job creation and poverty alleviation. The study identified factors such as access to finance, technology, and infrastructure that positively impact MSME performance (Utama et al, 2024) H5: Financial accessibility has a significant positive impact on MSME Performance.…”
Section: H4b: Growth Phases Of An Msme Have a Significant Positive Im...mentioning
confidence: 99%
See 2 more Smart Citations
“…MSMEs are generally labor-intensive so they absorb a lot of labor. The government needs to encourage the growth of MSMEs through ease of licensing, access to financing, training, and product marketing (Utama et al, 2023). MSMEs also need to continue to be empowered so that they can develop into medium and large businesses.…”
Section: Empowermentmentioning
confidence: 99%